AKUNTABILITAS DAN KAPABILITAS BANK SYARIAH (STUDI PADA BANK SYARIAH â€œXâ€ CABANG MALANG) - Fahrudin A, Ahmad (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2011)
The dynamics of development of Islamic banking in the working area KBI Malang is encouraging its development in which the Islamic banks NPL rate tends to increase significantly. In this institution within a period of nearly two years alone have been able to make an investment of about 13 M. with clients (depositors) of about 1300 people and 250 customers (users). This is the kind of qualitative research that uses a case study, the approach aims to maintain the integrity of the object and also with verifikatif approach. Verifikatif approach is intended to minimize the possibility of low reliability is often the case in case study research, in order to explain: first: accountability factors in the management of Islamic banks and funds processing, collection and utilization of capital funds, second: factors capabilities of Islamic banks in improving the quality and quantity of social and economic life of society. The results showed that: Factors that support the assessment of accountability in the management of Islamic banks and funds processing, collection and utilization of capital funds is reviewed from the aspect of increased cash liquidity ratio of 15.06% in 2005 rose to 18.12% in 2006 so it has good title, while LDR 44.12%, still well in the predicate. ROA profitability aspects seem to have decreased between 2005 to 2006, where in 2005 while the ROA of 1.99% in 2006 to 0.77%, to BOPO increase from the year 2005 amounted to 84.75% in 2006 amounting to 95.01%, for capital aspects of healthy and performing said, because the CAR above 10% which in 2005 grew 16.94% to 19.07%. Factors that support the capability of Islamic banks in improving the quality and quantity of social and economic life of society is: cooperation financing, business development and service cooperation, and cooperation through SME business support reached 42% this year. Â  Â